2009
DOI: 10.1007/s00423-009-0577-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbon dioxide pneumoperitoneum on hepatic function in obstructive jaundice: an experimental study in a rat model

Abstract: Alterations in hepatic function occur in pneumoperitoneum applied jaundiced subjects. However, there were no statistically significant differences between the groups 2 and 4 with regard to white blood cell and platelet counts, serum liver enzymes including AST, ALT, and total bilirubin values, MDA and GSH levels and SOD activity of liver homogenate, and histologic damage. These results indicate that there is no additional risk on liver function associated with pneumoperitoneum performed in obstructive jaundice. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Numerous experimental studies proved more intense oxidative stress and increased intensity of lipid peroxidation in the plasma and liver tissue in animals with experimentally induced cholestasis [6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental studies proved more intense oxidative stress and increased intensity of lipid peroxidation in the plasma and liver tissue in animals with experimentally induced cholestasis [6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, decreases in RBF and GFR are among the most common pathophysiological alterations in clinical and experimental jaundice and cirrhosis [46,47,86], suggesting that these clinical conditions may display an exaggerated renal vulnerability to increased IAP. In this context, Bostanci et al [87] have demonstrated that 12 mmHg pneumoperitoneum for 60 min in a rat model of obstructive jaundice resulted in moderate but nonsignificant increases in serum liver enzymes including AST, ALT, and total bilirubin values. However, this report did not refer to the renal effects of increased IAP in rats with obstructive jaundice.…”
Section: Pneumoperitoneum and Kidney Functionmentioning
confidence: 99%
“…The main advantages of this method include lower hospitalization duration, small incisions made during the surgery, fewer complications, and shorter recovery periods for the patients (1)(2)(3). According to the studies, the incidence of complications after laparotomic cholecystectomy is reported 5-17% (3,4,5), while it is decreased to 2-10% in the laparoscopic approach (1,2). Considering the mentioned advantages, laparotomic cholecystectomy is now approved as the gold standard treatment for symptomatic gallstone (1).…”
Section: Introductionmentioning
confidence: 99%